LISTA DE LAS ESPECIES CHILENAS DE LA FAMILIA VESPIDAE (HYMENOPTERA: VESPIDAE) (Acta Entomológica Chilena, 2022)
This paper presents a checklist of the currently recognized species of vespids in the chilean area.
Keywords: Vespidae, Hymenoptera, Systematics, Chile